Recommendations for enhancing research outcomes and the efficacy of transcranial direct current stimulation in post-stroke motor rehabilitation for local settings - Sim, Sze Kiat (Malaysian Medical Association, 2025)
Transcranial direct current stimulation (tDCS) has emerged as a potential adjunct therapy for post-stroke motor rehabilitation. While conventional rehabilitation methods remain the primary approach to improving motor function after stroke, many patients experience incomplete recovery, necessitating the exploration of additional interventions. This commentary article examines the role of tDCS in poststroke motor recovery, focusing on its mechanisms, efficacy, and limitations. Herein, the variability in research findings and individual patient responses as well as the recommended methods for optimising tDCS use in local clinical settings are highlighted.